Protective effect of Propolfenol® on induced oxidative stress in human spermatozoa. (3rd May 2017) - Biagi, M.; Collodel, G.; Corsini, M.; Pascarelli, N. A.; Moretti, E.
Summary: The propolis extract was shown to possess the capacity to protect sperm membrane from the deleterious action of oxidative attack. Oxidative stress can induce propagation of a lipid peroxidation (LPO) chain reaction because spermatozoa contain high concentration of unsaturated fatty acids. This study aimed at evaluating in vitro the possible toxicity and/or the antioxidant properties of Propolfenol ® in ejaculated human spermatozoa. A colorimetric assay determined the total flavonoid content by spectrophotometry and a high‐performance liquid chromatography–diode array detection analysis the quantity of galangin, pinocembrin and caffeic acid phenylethilic ester (CAPE). Sperm parameters such as motility, vitality and DNA integrity were assessed utilising optical microscopy. The antioxidant properties Propolfenol ® against LPO induced by tert‐Butyl Hydroperoxide were evaluated using the C11‐BODIPY581/591 probe. Chemical analysis of Propolfenol ® revealed low quantities of galangin, pinocembrin and CAPE; cyclic voltammetry experiments showed that Propolfenol ® may exert an antioxidant activity. A protective action of Propolfenol ® (20 and 100 μg/ml) on induced LPO in human spermatozoa was detected. Propolfenol ® may be proposed as the supplement in media for sperm preparation techniques or cryopreservation to counteract the increased presence of reactive oxygen species generated by these methods.